Applied Model of Nutrient Oxidation in Male Broilers Reared under Different Temperatures - Maksudi, Maksudi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
Effects of the environmental temperatures on nutrient oxidation were evaluated in male broiler  chickens.  The  chickens  were  allocated  into twelve  cages  with  six  chickens  per  cage during  the  first  week  and  three  chickens  in  the  following  five  weeks  of  experiment.  The temperatures  were  set  on  T0  =  21o C,  T1  =  24oC,  and  T2  =  28oC.  A  22  to  24$hour$respiration measurement  was  made  in  the  middle  of  each  five$day  collection  period  using  an  open$air circulation  respiration  unit.  The  results  showed  that  the  increase  of  temperature  decreased protein  (OXP)  and  fat  oxidation  (OXF;  P<0.05),  but there  was  no  difference  (P>0.05)  on carbohydrate  oxidation  (OXCHO).  Lipogenesis  from  carbohydrate  made  up  the  main constitution (69 to 78%) to  the total fat retention. In contrast, fat retention from  protein (8.8 to 9.6)  was  the  minor  contribution,  and  there  was  no  difference  (P<0.05)  among  the  groups. Furthermore,  the  conversion  of  dietary  fat  to  the  fat  retention  was  increased  (12.1  to  21.4) following the increase of the environment temperature. In conclusion, the temperature range of 21 to 28oC used was still in the tolerable hot zone since the oxidation of protein, carbohydrate and  fat  were  not  influenced.  However,  the  utilization  of  protein  and  fat  depended  on  the environmental temperature except for carbohydrate.